Seabirds under environmental pressures: Food supplementation has a larger impact than selenium on chicks exposed to mercury and a viral disease - Sebastiano, Manrico; Eens, Marcel; Bustamante, Paco; Chastel, Olivier; Costantini, David (Frontiers in Ecology and Evolution, 2022)
Although infectious disease outbreaks represent a serious threat for wildlife population viability, the environmental factors that underlie such outbreaks are poorly investigated. The French Guiana breeding population of Magnificent frigatebird Fregata magnificens, is subjected to recurrent episodes of chicks’ mortality likely caused by a viral disease. We hypothesized that high mercury (Hg) concentrations may be responsible for the emergence of clinical signs. We therefore investigated whether healthy and sick chicks show different Hg concentrations in blood. Because the essential element selenium (Se) may be highly depleted during Hg poisoning, we further experimentally tested whether an increased intake of dietary Se has an effect on blood levels of Hg, increases circulating Se, and improves the oxidative status of chicks. Finally, we compared the results of this experiment with a previous food supplementation experiment. Our results show similar Hg concentrations between healthy and sick chicks with visible clinical signs of the disease. Se concentrations were significantly depleted in sick chicks. Both the Se and fish supplementation experiments significantly increased Se concentrations in blood, while Hg levels were only modestly affected. Providing food to chicks appeared to have greater benefits than only supplementing chicks with Se pills as, although food supplementation had an impact on blood Se similar to that of supplementation with Se pills, it also reduced the vulnerability of chicks to the viral disease, possibly by reducing nutritional stress and providing essential nutrients.